29.0k views
3 votes
Level: Standard
2) Given: -2(x - 4) = 3(x + 12); Prove: x = -5.6
Statements
Reasons​

Level: Standard 2) Given: -2(x - 4) = 3(x + 12); Prove: x = -5.6 Statements Reasons-example-1
User LorDex
by
5.3k points

2 Answers

6 votes

Answer:

comments r full

Explanation:

User Deloris
by
5.2k points
4 votes

Answer:

hsishisnsidhidhdidjjxnxindidhdinsixhxkxjosjskxijxhsishodjdixjishs

User Pigfly
by
6.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.